Lubrication fundamentals - Will, J. George (Mechanical engineering (Marcel Dekker, Inc.), 1980)
Building on the cornerstone of the first edition, Lubrication Fundamentals Second Edition outlines the emergence of higher performance-specialty application oils and greases and emphasizes the need for lubrication and careful lubricant selection. Thoroughly updated and rewritten since the previous edition reached its 10th printing, the book discusses product basics, machine elements that require lubrication, methods of application, lubricant storage and handling, and lubricant conservation. Keeping the characteristics that made the first edition a classic reference, this second edition provides current information in the format readers have come to trust.